Pengaruh Return On Equity (ROE), Return On Invesment (ROI) Terhadap Nilai Pasar Dengan Price Book Value (PBV) Pada Industri Manufaktur (Studi Kasus Pada Perusahaan Manufaktur di Indonesia Yang Terdapat di BEI Periode 2012 - 2014) - Suryaningsih, Agustina; , Dr. Syamsudin, MM (2016)
This study aims to analyze (1) To analyze the effect of Return On Equity (ROE) for the market value of Price Book Value (PBV) in the manufacturing industry. (2) To analyze the effect of the Return On Investment (ROI) on the market value of Price Book Value (PBV) in the manufacturing industry. (3) To analyze the effect of Return On Equity (ROE), Return On Investment (ROI) on the market value of Price Book Value (PBV) in the manufacturing industry. Selected population in this research is manufacturing companies listed in Indonesia Stock Exchange 2012-2014 period as many as 57 companies. The analytical method used classic assumption test including normality test. Autocorrelation test, test and test mutikolinearitas heterokodastisitas. By hypothesis testing using partial significance (t-test) and test of significance together (Test-F) and the coefficient of determination (R2). Results showed ROE significantly influence the market value (price book value) with the calculated tcount (7.033) with a significance of 0.000 which is smaller than 0.05 then Ho is rejected. In the variable ROI significant effect partially on the market value (price book velue) with the calculated tcount (.136) with a .892 significance smaller than 0.05 then Ho is accepted. Based on test results obtained value F obtained Fhitung (133.520) with probability 0.000 <0.05 it indicates that the ROE and ROIsudah precisely measure the dependent variable so that the regression model is already fit. Nilai coefficient of determination (R2) of 0.832. This means that 83.2% of the variation is explained by the variation PBV change in ROE and ROI. While the balance of 16.8% is explained by other Factors not participate observed. Keywords: return on equity, return on investment, price-book value, market value